Aspectos emocionais investigados na infertilidade através do método de Rorschach - Motooka, Rita de Cássia Ferrer da Rosa (2008)
This research was made with a group of 15 women enrolled in the Assisted Reproduction Program of the Perola Byington Hospital, and aimed to investigate the psychism of infertile women through the Rorschach method (Comprehensive System). The research protocol was designed to collect data about infertility s emotional aspects and how women deal with them. The members of the group participated in a semi-structured interview and in a test using the Rorschach method. This study covered questions about the feminine principle, the initial phases of the human development and showed, briefly, some aspects of the role the woman have been playing in our society. The theory utilized in this study was based on the Analitical Psychology by Carl Gustav Jung, and the depressed and disphoric content, as well as the stress manifestation, were verified by using the projective test of Rorschach method, developed by Hermann Rorschach. The analisys of the results provided by the Rorschach method reinforced former studies results that pointed to the presence of stress and depression in women under assisted reproduction procedures. The categorization of the semi-structured interview data highlighted painful aspects and the strong impact these women suffered